OrganoCat pretreatment of perennial plants: Synergies between a biogenic fractionation and valuable feedstocks. (November 2017) - Damm, Tatjana; Grande, Philipp Michael; Jablonowski, Nicolai David; Thiele, Björn; Disko, Ulrich; Mann, Ulrich; Schurr, Ulrich; Leitner, Walter; Usadel, Björn; Domínguez de María, Pablo; Klose, Holger
Graphical abstract: Elucidating holistic biomass processibility: OrganoCat pretreatment of perennial plants. Highlights: First successful application of biogenic OrganoCat pretreatment on perennial biomass. High fractionation efficiency for grass-biomass. Highest pretreatment effect for Szarvasi. Abstract: A successful biorefinery needs to align suitable pretreatment with sustainable production of biomasses. Herein, four perennial plants, (Sida, Silphium, Miscanthus and Szarvasi) regarded as promising feedstocks for biorefineries were subjected to the OrganoCat pretreatment. The technology was successfully applied to the different perennial plants revealing that pretreatment of grasses was more efficient than of non-grasses. Thorough analyses of the lignocellulose – before and after fractionation – enabled a detailed description of the fate of cellulosic, non-cellulosic polysaccharides and lignin during the pretreatment. Especially Szarvasi pulp displayed outstanding results in terms of fractionation efficiency and enzymatic digestibility, though in all cases successful lignocellulose fractionation was observed. These insights into the structural composition of different perennial plant species and the impact of the OrganoCat pretreatment on the plant material leads to useful information to strategically adapt such processes to the individual lignocellulosic material aiming for a full valorisation.